ON THE BASIS OF GENERAL DERIVATIVE UNITY OF TRIGANOMETRIC DISTRIBUTION OF FUNCTIONS (Scientific journal of the Fergana State University, 2023)
The article discusses the issue of ensuring the uniqueness of this distribution when distributing complex functions of various types over rows. For this purpose, the concept of a generalized derivative is used; it is shown that the generalized derivative in some cases coincides with the generalized derivative of the 2nd order and a simple derivative at unknown points.